Combination Therapy of Temporary Tracheal Stenting and Radiofrequency Ablation for Multinodular Thyroid Goiter with Airway Compression - Shin, Ji Hoon (The Korean Society of Radiology, 2013)
We report a case of multinodular thyroid goiter in an 80-year-old man who successfully underwent tracheal stent placement for respiratory distress caused by the thyroid goiter and following two radiofrequency (RF) ablation sessions performed for thyroid volume reduction. This sequential treatment allowed elective stent removals four weeks after the second RF ablation session because the thyroid volume had been progressively reduced. Combination therapy of temporary airway stenting and RF ablation for the treatment of thyroid goiter has two advantages, i.e., immediate reliefs of dyspnea with airway stenting and reductions of the thyroid volume with RF ablation, and thus, allowing symptom reliefs even after the stent removals.